A Total Economic Valuation of Wetland Ecosystem Services: An Evidence from Jagadishpur Ramsar Site, Nepal - Sony Baral; Bijendra Basnyat; Rajendra Khanal; Kalyan Gauli (The Scientific World Journal)
Wetlands are the most productive ecosystem and provide wide arrays of wetland ecosystems (goods and services) to the local communities in particular and global communities in general. However, management of the wetland often does not remain priority and recognized as the unproductive waste land mainly due to poor realization of the economic value of the wetlands. Taking this into account, the study estimated the total economic value of the Jagadishpur Reservoir taking into account direct, indirect, and nonuse value. The study prioritized six major values of the reservoir which include wetland goods consumption, tourism, irrigation, carbon sequestration, biodiversity conservation, and conservation for future use (existence and option value). The study used market and nonmarket based valuation techniques to estimate total economic value of the reservoir. Household survey, focus group discussions, and interaction with the tourism entrepreneurs and district stakeholders were carried out to collect information. The study estimated the total annual economic value of the reservoir as NRs 94.5 million, where option/existence value remains main contributor followed by direct use value such as wetland goods and tourism and indirect use value, for example, carbon sequestration, biodiversity conservation, and irrigation. The study reveals that the local communities gave high importance to the future use value and are willing to make investment for conservation and restoration of reservoir given its conservation significance.